Methods and indicators to validate country reductions in incidence of hepatitis C virus infection to elimination levels set by WHO. (April 2022) - Artenie, Adelina; Luhmann, Niklas; Lim, Aaron G; Fraser, Hannah; Ward, Zoe; Stone, Jack; MacGregor, Louis; Walker, Josephine G; Trickey, Adam; Marquez, Lara K; Abu-Raddad, Laith J; Ayoub, Houssein H; et al.
Summary: One of the main goals of the 2016 Global Health Sector Strategy on viral hepatitis is the elimination of hepatitis C virus (HCV) as a public health problem by 2030, defined as an 80% reduction in incidence and 65% reduction in mortality relative to 2015. Although monitoring HCV incidence is key to validating HCV elimination, use of the gold-standard method, which involves prospective HCV retesting of people at risk, can be prohibitively resource-intensive. Additionally, few countries collected quality data in 2015 to enable an 80% decrease by 2030 to be calculated. Here, we first review different methods of monitoring HCV incidence and discuss their resource implications and applicability to various populations. Second, using mathematical models developed for various global settings, we assess whether trends in HCV chronic prevalence or HCV antibody prevalence or scale-up levels for HCV testing, treatment, and preventative interventions can be used as reliable alternative indicators to validate the HCV incidence target. Third, we discuss the advantages and disadvantages of an absolute HCV incidence target and suggest a suitable threshold. Finally, we propose three options that countries can use to validate the HCV incidence target, depending on the available surveillance infrastructure.